Recurrent Somatic TET2 Mutations in Normal Elderly Individuals With Clonal Hematopoiesis - Busque, Lambert (2012)
Aging is characterized by clonal expansion of myeloid-biased hematopoietic stem cells and by an increased risk of myeloid malignancies. Exome sequencing of 3 elderly females with clonal hematopoiesis demonstrated by X-inactivation analysis identified somatic TET2 mutations. Recurrence testing found TET2 mutations in 10 out of 182 individuals with X-inactivation skewing. TET2 mutations were specific to individuals with clonal hematopoiesis without hematologic malignancies and were associated with alterations in DNA methylation.